BARBERSHOP BUSINESS DEVELOPMENT IN MSMES IN PEMATANG SIANTAR CITY - Berutu, Njuah Assiddiq; Syah, Amirul (Proceeding International Seminar of Islamic Studies, 2024)
The growth of MSMEs continues to increase every year, but in 2022 it will experience a decline. North Sumatra is one of the provinces with the largest number of MSME developments in Indonesia. Barbershop growth continues to increase as a result of changes in people's lifestyles. The facilities and services offered greatly influence customer interest in the Barbershop. The aims of this research are (1) Carrying out a descriptive economic analysis of the UMKM production sector in Pematang Siantar (2) Carrying out an economic evaluation of the actors in the Barbershop UMKM sector in meeting family income in Pematang Siantar City. This research uses a qualitative approach. Technique sampling in this research that is with method snowball sampling use questionnaire Which given to 30 perpetrator MSME Barbershop in City Pematang Siantar. The data collection technique used in this research comes from websites official like Body Center Statistics (BPS), Ministry Trading, and distribution of questionnaires via Google Form . Data analysis techniques used in this research uses analysis factors with program Smart PLS 3.0. results study shows that Number of Customers and Facilities Factors influential and significant on business development for UMKM Barbershop operators in Pematang Siantar City to meet economic income.